2017
DOI: 10.1530/rep-16-0657
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CART in ewes with differing ovulation rates

Abstract: We hypothesised that cocaine- and amphetamine-regulated transcript () would be differentially expressed in ewes with differing ovulation rates. Expression of mRNA for , as well as, , and was determined in antral follicles ≥1 mm in diameter collected during the follicular phase in ewes heterozygous for the Booroola and Inverdale genes (I+B+; average ovulation rate 4) and ++ contemporaries (++; average ovulation rate 1.8). In ++ ewes ( = 6), was expressed in small follicles (1 to<3 mm diameter), where 18.8 ± 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
(27 reference statements)
0
13
2
Order By: Relevance
“…In addition, the expression of GHR was not correlated with the change of insulin-like growth factor (IGF-I) concentration postpartum in the liver [20]. FSHR has significance regarding the modulation of animal reproductive functions [10,23]. Moreover, previous studies found that the FSH could accelerate the maturation rate of sheep oocytes and reduce their apoptosis rate, increase the expression levels of FSHR, LHR and gonadotropin releasing hormone receptor (GnRHR) mRNAs, and strengthen expressions of FSHR and GnRHR proteins [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of GHR was not correlated with the change of insulin-like growth factor (IGF-I) concentration postpartum in the liver [20]. FSHR has significance regarding the modulation of animal reproductive functions [10,23]. Moreover, previous studies found that the FSH could accelerate the maturation rate of sheep oocytes and reduce their apoptosis rate, increase the expression levels of FSHR, LHR and gonadotropin releasing hormone receptor (GnRHR) mRNAs, and strengthen expressions of FSHR and GnRHR proteins [21].…”
Section: Introductionmentioning
confidence: 99%
“…McNatty et al () suggested that the differences in the hormone profile may be attributed due to the effect of FecB genotypes before and after the puberty, ovarian follicular development, gonadotrophin secretion and the pituitary response to gonadotropin‐releasing hormone (GnRH). A recent study also showed a similar progesterone concentration in heterozygous Inverdale/Booroola (I+B+) and non‐carrier genotypes before and after 12 hr of initiation of follicular phase (Juengel et al, ). Thus, it is inferred from the above discussion that the effect of FecB mutation on progesterone secretion in carrier and non‐carrier ewes is not so noticeable.…”
Section: Discussionmentioning
confidence: 71%
“…This has been observed when examining the mRNA encoding LHCGR or the ability of the cells to bind and respond to LH, as assessed by cAMP production (McNatty et al, , 2017Crawford et al, 2011;Juengel et al, 2017). Similarly, in cows carrying a copy of the Trio mutation, which have increased expression of mRNA encoding the inhibitory SMAD6 (Kamalludin et al, 2018), thus postulated reduced BMP signalling, follicles have an earlier responsiveness to LH with increased expression of the LHR in the granulosa cells (Garcia-Guerra et al, 2018a).…”
Section: Effects On Responsiveness To Fsh and Lhmentioning
confidence: 99%
“…FSH responsiveness, as measured by mRNA encoding FSHR or the ability of the cells to bind and respond to FSH in general, is not different between control ewes and ewes carrying the Inverdale and/or Booroola mutations (McNatty et al, , 2017Crawford et al, 2011;Juengel et al, 2017). Similarly, cows carrying the Trio mutation do not have differential expression of FSHR mRNA compared to non-carrier controls (Garcia-Guerra et al, 2018a).…”
Section: Effects On Responsiveness To Fsh and Lhmentioning
confidence: 99%
See 1 more Smart Citation